Numerical Study of the Impingement of Water Film on a Small Attached Bulging Plate on a Vertical Plane - Hu, Po; Hu, Zhen (Frontiers in Energy Research, 2021)
In the passive containment cooling system of AP1000, the condensed water is expected to flow down on the inner surface of the steel wall of the containment, and recover to the in-containment refueling water storage tank (IRWST), therefore, to maintain the long-term coolability of the passive residual heat removal system. However, there are attached bulging plates on the inner surface for various engineering needs, such as supporting, and the impingement of condensed water film on these bulging plates can reduce the amount of the recovered water. In this article, a 3-D Eulerian wall film model in FLUENT was used to study a series of flow behaviors when a water film impinged on the bulging plate on a plane surface. The loss ratio of falling film impinging on attached plates of different sizes under different flow rates were calculated and in good agreement with the experiment results. Four stages of the film behavior during the impingement were identified and analyzed; in addition, the influences of the bulging height of attached plate and flow rate were studied. And a correlation between the loss ratio of impinging water film, the bulging height of the attached plate, and the Weber number was obtained.